Campaigns and Operations: Selected Bibliographies - Loughran, Amy; Lowe, Areena; Nicula, Gail; Orr, Carolyn; Oswitt, Jane (1989)
This bibliography provides selected citations to major military operations, primarily in World War II. They include: Battle of Britain, Battle of the Atlantic, Central Pacific (General), China-Burma-India Theatre, Coral Sea, France (Includes Anvil & Dragoon), Guadalcanal, Italy (includes Anzio, Cassino), Kursk (Emphasis on July 1943), Leyte, Midway, New Guinea, North Africa, Okinawa, Operations, Barbarossa (Initial Offensive, June 1941-Winter 1941), Garden, Market, Torch, Ploesti, Rabaul, Remagen, Schweinfurt, Sicily (Operation Husky), Stalingrad, and Tokyo bombing raids. Also covered are: The 1973 Arab-Israeli war; Falkland Islands, Gallipoli, and Tannenberg in WWI, Korean War, Pacific regions pre-WWII, and Campaign scenarios for the Horn of Africa and the Angolan-Cuban connection, the Northwest Pacific area, and the Syria-Israel tinderbox. (edc)